2011
DOI: 10.22201/fi.25940732e.2011.12n3.027
|View full text |Cite
|
Sign up to set email alerts
|

Identificación de regiones hidrológicas homogéneas mediante análisis multivariado

Abstract: ResumenLa regionalización hidrológica se utiliza para transferir información de cuencas aforadas a las no aforadas. Sin embargo, para obtener resultados confi ables, las cuencas involucradas deben tener un comportamiento hidrológico semejante. El objetivo de este trabajo fue identifi car zonas hidrológi-camente homogéneas en la Mixteca oaxaqueña y zonas aledañas. El área de estudio comprendió 17 subcuencas para las que se cuantifi caron 20 variables climáticas y fi siográfi cas potencialmente útiles en la pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Ouarda et al (2008) used statistical analysis to estimate homogeneous hydrological regions for regionalization and found that Canonical Correlation Analysis (CCA) outperformed Canonical Kriging and hierarchical clustering for three basins in Mexico. Álvarez-Olguín et al (2011) also applied homogeneous hydrological region analysis tools on 17 catchments in the Iberian Peninsula in Mexico and found that they could be grouped into three classes. Based on this work, Domínguez-Mora et al (2016) developed a procedure to regionalize maximum flows on 37 catchments in Mexico, and Allende et al (2009) performed regionalization on a catchment undergoing land-use change but limited the analysis to two years.…”
Section: Regionalization In Mexico and Study Objectivesmentioning
confidence: 99%
“…Ouarda et al (2008) used statistical analysis to estimate homogeneous hydrological regions for regionalization and found that Canonical Correlation Analysis (CCA) outperformed Canonical Kriging and hierarchical clustering for three basins in Mexico. Álvarez-Olguín et al (2011) also applied homogeneous hydrological region analysis tools on 17 catchments in the Iberian Peninsula in Mexico and found that they could be grouped into three classes. Based on this work, Domínguez-Mora et al (2016) developed a procedure to regionalize maximum flows on 37 catchments in Mexico, and Allende et al (2009) performed regionalization on a catchment undergoing land-use change but limited the analysis to two years.…”
Section: Regionalization In Mexico and Study Objectivesmentioning
confidence: 99%